Análise da qualidade da propagação do sinal UHF na cidade de Uberlândia, utilizando os modelos de propagação ITU-R P.1546, Okumura-Hata e Log Distância - Santos, Tiago Nunes (2016)
With the advent of new technologies, the TV had enhanced transmission processes, from analog signal to digital, bring great benefits to the viewers from the image quality, audio 5.1, interactivity, the presence of adjacent channels, multiple programming and mobile devices. All these benefits are possible due to better spectrum utilization and digital technology. However, television stations in Brazil will face many challenges in the implementation of digital system: will have to keep the scope of the analog signal with digital technology; keep signal quality at different points of the city; good signal reception indoors where there is no external antenna UHF, and mobile reception with high quality. Moreover, with the growth of the civil construction sector in Brazil has expanded the number of obstacles between the transmitter and receiver. Thus, there were other forms of interference in the spread as reflection, refraction and scattering, caused mainly by the terrain profile, buildings and other obstacles present on the route. Accordingly, the stations must make constant the signal propagation survey for possible shadow regions in the city, in order to implement signal repeaters in the region. Another analysis that can be done is to use spread software capable of plotting the spots of the UHF and VHF signal in order to choose the best propagation method to be adopted to reach a more realistic / accurate model. With the transition from analog to digital technology and the shutdown of the analog signal provided for 2018 in Uberlândia a study of the quality of the digital TV signal will be needed in this city, with measurements of the intensity of the digital signal in various city points and an analysis of the project technician with the measured value in the field. In this sense, this work aims to collect electric field data and electrical power digital terrestrial television signal in urban areas of Uberlândia, Minas Gerais, and thus make comparisons of the measured values with the theoretical of propagation models ITU-R P .1546, Okumura-Hata and Log-Distância of operating TV stations the digital signal in the city.